Halomonas sp. MC140, a polyhydroxyalkanoate (PHA) producer isolated from the Arctic environment - Mikkel Christensen; Iulia Chiciudean; Irina Lascu; Piotr Jablonski; Volha Shapaval; Boris Zimmermann; Ana-Maria Tanase; Hilde Hansen (Scientific Reports)
Abstract Polyhydroxyalkanoates (PHA) are biobased and biodegradable polyesters with potential to replace petroleum-based plastics or for use as feed in aquaculture. In this study, Halomonas sp. MC140 was isolated from the Arctic littoral environment in Norway and characterized in terms of PHA production. Phylogenetic analysis of the draft genome sequence placed the strain as closely related to Halomonas profundi MT13. A genome-based model of PHA biosynthesis pathways was constructed, and shake-flask experiments identified the highest PHA production in the form of polyhydroxybutyrate (PHB) with acetate (35 ± 4.8%) or glucose (28 ± 7.9%) supplementation, as verified by gas chromatography-flame ionization detector (GC-FID) analysis, while the addition of propionate produced PHB-co-valerate (PHBV) co-polymer (≈ 1% 3-HV). Low PHB production (< 5%) was found from supplementation with glycerol or fructose. A multivariate Partial Least Squares Regression (PLSR) model for low- to medium-range (0–40%) PHB content in Halomonas sp. MC140 was constructed with Fourier transform infrared spectroscopy (FTIR) spectra and used to assess PHA production over time. Additionally, the strain’s carbon substrate utilization phenotype was characterized using the Biolog assay. These findings suggest that PHA production by Halomonas sp. MC140 is modest compared to other Halomonas species but provides a starting point for optimization or use in sustainable feed applications in Norwegian aquaculture, where lower PHA production is sufficient compared to bioplastic production.